Contribution to society in national development: a case of Malaysian government retirees - Yahya, Khulida Kirana; Johari, Johanim; Adnan, Zurina; Mohd Isa, Mohd Faizal; Daud, Zulkiflee (Universiti Utara Malaysia, 2008)
The number of Malaysian senior citizens is expected to rise to 2.71 million by the year 2020. By then, Malaysia will be an ageing society, which includes the government retirees who have reached their mandatory retirement age of 56 years old. The objective of this study was to determine the type of contribution the government retirees in Malaysia are able to provide to society and subsequently to the nation as a whole. Given this, a total of 1609 questionnaires were gathered and analysed using SPSS. Findings indicated that most of the retirees have acquired vast skills and other characteristics throughout their years of service, especially in the area that relates to their years of service, especially in the area that related to their tasks and responsibilities. However, these retirees are unable to transfer their invaluable skills and other characteristics appropriately, once they have retired. It is therefore of paramount importance for the government and non-goverment bodies to develop a proper means for these retirees to utilise their skills. Recommendations bring to fore several policy guidelines and activities, such as retirees' involvement in businesses,flexible reemployment programnes, and various social rehabilition programmes. These measures can be undertaken by the relevant authorities to help government retirees optimise their skills and other characteristics for national development.